Pemanfaatan Limbah Bongkol Jagung Untuk Pembuatan Briket Arang Sebagai Potensi Energi Alternatif - Abubakar Sidik Katili; Yuliana Retnowati; Ilyas H Husain (Univeristas Negeri Gorontalo, 2021)
The purpose of this program to provide knowledge and skills to the SP3 Saritani community in utilizing agricultural waste of corn cob as the basic ingredients of charcoal briquettes as an alternative energy. External targets of this program include opportunities for students to learn with the community about village development (learning society). To implementation in this activity used Focus group discussion (FGD) between students and partner groups. Direct observation and excavations together with partners and document the potential resources that will be developed with the assisted community. Designing scenarios for the implementation of the program, conducting training and mentoring for the processing of agricultural waste of corn cobs for raw materials of charcoal briquette production as an alternative energy potential. The result obtained is the existence of charcoal briquette products made from corn waste. Charcoal briquettes produced have physical characteristics that are ideal enough as an alternative fuel. The physical shape of charcoal briquettes in the form of cylinders with a height of about 3 cm and a diameter of about 5 cm and hard enough with a type of starch adhesive with a percentage of 5%, 10% and 15% respectively. The test results concluded that the process of ignition of briquettes into coals that are ready for use takes only one minute. The impact obtained is the value of products produced to provide economic independence to the SP3 Saritani community. This devotional activity has also supported the application of innovations and technologies that are directly useful in achieving SDGs on the 7th goals (clean and renewable energy villages) and the 15th goals (villages care about the land environment).